2012
DOI: 10.17221/5562-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for female fertility and milk production traits in first-parity Czech Holstein cows

Abstract: ABSTRACT:The aim of this study was to estimate genetic parameters for female fertility and production traits in first-parity Czech Holstein cows and to quantify the effect of using this information on the accuracy of a selection index in seven different scenarios. In order to estimate genetic (co)variance components, the DMU software running an AI-REML algorithm was used. The analyses were made using a series of bivariate animal models. The pedigree included 164 125 animals and it was set up using a pruned ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
38
2
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 19 publications
14
38
2
3
Order By: Relevance
“…These are higher than previous estimates from Czech data by Dědková and Wolf (2001), who found heritabilities of 0.28, 0.24, and 0.25, and higher than those of Zink et al (2012), who reported 0.21, 0.21, and 0.23 for MY1, FY1, and PY1, respectively.…”
Section: Heritabilitycontrasting
confidence: 74%
See 1 more Smart Citation
“…These are higher than previous estimates from Czech data by Dědková and Wolf (2001), who found heritabilities of 0.28, 0.24, and 0.25, and higher than those of Zink et al (2012), who reported 0.21, 0.21, and 0.23 for MY1, FY1, and PY1, respectively.…”
Section: Heritabilitycontrasting
confidence: 74%
“…These estimates are slightly higher than those of Zink et al (2012), who reported 0.04, 0.04, and 0.03 for CFI1, DO1, and FLI1, respectively, for Czech Holsteins. Current results are, however, concurrent with other recent research.…”
Section: Heritabilitycontrasting
confidence: 71%
“…bull semen, sperm survival, cold shock, extender, LDL cholesterol Fertility of dairy cows has declined over the past fi ve decades as milk production per cow has increased (Zink et al, 2012;Walsh et al, 2011). The issue of cattle fertility was intensively studied in recent years from cow point of view and eff ects on their reproductive performance (Doležalová et al, 2013;Roche et al, 2011;Hanuš et al, 2010;LeBlanc et al, 2010).…”
mentioning
confidence: 99%
“…Zink et al (2012) determined the genetic parameters for female fertility in relation to the accuracy of the selection index under different scenarios, when Šafus et al (2005) stated the necessity of incorporating breeding values for reproduction traits into the Czech selection indexes for the Holstein breed based on the BV for milk production. The average BV in dairy cows flushed during individual seasons fluctuated only within the range of 69-293 kg.…”
Section: Discussionmentioning
confidence: 99%